Prediction of Residual Stresses During the Hot Forging Process of Spherical Shells Based on Microstructural Evolution - Yupeng Wu; Jiasheng Li; Zhaocheng Wei; Yuxin Fang; Hongxia Li; Ming Huang (Journal of Manufacturing and Materials Processing)
A unified viscoplastic constitutive model based on internal physical variables was proposed to predict the viscoplastic mechanical behavior and microstructure evolution of metals during hot forging. Based on the phase transformation theory of materials under the effect of temperature, the evolution mechanism of residual stress during the cooling process after hot forging and stamping was explored. The determined unified viscoplastic constitutive equation was written in the VUMAT subroutine and employed for the explicit FE analysis of the hot forging and stamping process of thin-walled spherical shells. In the data transfer process, the stress field, temperature field, and deformation characteristics calculated during the high-temperature transient of the hot forging and stamping process were inherited. Meanwhile, the thermoplastic constitutive equation considering the influence of phase transformation was written in the UMAT subroutine and utilized for the implicit FE analysis of the cooling process of thin-walled spherical shells. Through comparison with the measured stress results of the spherical shells after actual forging, it was shown that the proposed constitutive model can effectively predict the microstructural evolution and the final residual stress distribution pattern of medium-carbon steel during the hot forging process.